2022
DOI: 10.1002/edn3.362
|View full text |Cite
|
Sign up to set email alerts
|

Assessing flower‐visiting arthropod diversity in apple orchards through metabarcoding of environmental DNA from flowers and visual census

Abstract: Arthropods are essential in maintaining healthy and productive agricultural ecosystems. Agricultural crops such as apples are typically pollinated by domesticated honey bees, but wild bees and other arthropod flower visitors also contribute to pollination. Flower visitors can also be natural enemies of crop‐pests or herbivores. Biodiversity is under pressure and knowledge of wildflower visitors is an important tool in designing orchards that can support high functional biodiversity. In our study, we assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 110 publications
1
8
0
Order By: Relevance
“…Here, we show that when combined with traditional survey methods, metabarcoding of eDNA collected from flowers can increase the number of arthropod families detected by 25%. Consistent with previous studies, eDNA metabarcoding allowed efficient and reliable detections of potential pollinators, as well as plant pests and parasites without the need for extensive taxonomic expertise (Gamonal Gomez et al, 2023; Johnson et al, 2023; Newton et al, 2023). The accuracy of this molecular method is, however, dependent on the quantity and quality of arthropod eDNA, the presence of non‐target DNA contamination, the sequence analysis method chosen, and the availability of arthropod sequences in online databases (Evans & Kitson, 2020; Ficetola et al, 2016; Valentin et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Here, we show that when combined with traditional survey methods, metabarcoding of eDNA collected from flowers can increase the number of arthropod families detected by 25%. Consistent with previous studies, eDNA metabarcoding allowed efficient and reliable detections of potential pollinators, as well as plant pests and parasites without the need for extensive taxonomic expertise (Gamonal Gomez et al, 2023; Johnson et al, 2023; Newton et al, 2023). The accuracy of this molecular method is, however, dependent on the quantity and quality of arthropod eDNA, the presence of non‐target DNA contamination, the sequence analysis method chosen, and the availability of arthropod sequences in online databases (Evans & Kitson, 2020; Ficetola et al, 2016; Valentin et al, 2021).…”
Section: Discussionsupporting
confidence: 79%
“…It has been widely used to monitor aquatic and terrestrial systems (e.g. Capo et al, 2021; Clare et al, 2021; van der Heyde et al, 2020), but studies of plant–animal interactions using eDNA extracted from flowers are rare (Gamonal Gomez et al, 2023; Johnson et al, 2023; Newton et al, 2023; Thomsen & Sigsgaard, 2019), and few have systematically compared metabarcoding of arthropod DNA on flowers to other survey methods, despite alternative approaches potentially detecting different taxa (Gamonal Gomez et al, 2023; Newton et al, 2023). We compared two commonly used arthropod survey methods—pan traps and DVR devices—with two common eDNA barcoding assays, to detect a wide range of arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…While the ability to detect insect visits to flowers using eDNA shows promise (Evans & Kitson, 2020; Gamonal Gomez et al, 2022; Harper et al, 2022; Thomsen & Sigsgaard, 2019), the technique has only recently been used to identify vertebrate flower visitors (Jønsson et al, 2023; Walker et al, 2022). Furthermore, while eDNA metabarcoding surveys have been shown to outperform the use of both visual (Barata et al, 2020) and camera trap (Leempoel et al, 2020) techniques in other contexts, there are limitations of the method, including limited knowledge on the deposition and persistence of eDNA on floral surfaces (Barnes & Turner, 2016; Harrison et al, 2019; Valentin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite only detecting 19 arthropod taxa between the two methods, the authors found these two methods to be complementary, with eDNA metabarcoding detecting pollinators, pests, and most species but lacking abundance data. As studies continue to explore residual arthropod eDNA on flowers, it is vital that comparisons between conventional methods and eDNA are conducted to ensure survey methods are maximizing arthropod detection (Gomez et al, 2023; Thomsen & Sigsgaard, 2019). To the best of our knowledge, no studies have compared metabarcoding residual arthropod eDNA from flowers with camera trapping approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Harper et al (2023) assessed how residual arthropod eDNA on flowers can evaluate pollinator species, while also testing various methods of eDNA collection and extraction to maximize arthropod communities detected. The latest paper by Gomez et al (2023) compared arthropod flower visitors in an apple orchard with DNA metabarcoding and visual assessments. Despite only detecting 19 arthropod taxa between the two methods, the authors found these two methods to be complementary, with eDNA metabarcoding detecting pollinators, pests, and most species but lacking abundance data.…”
Section: Introductionmentioning
confidence: 99%